2013
DOI: 10.1017/s0022215113000364
|View full text |Cite
|
Sign up to set email alerts
|

Pre-emptive triple analgesia protocol for tonsillectomy pain control in children: double-blind, randomised, controlled, clinical trial

Abstract: The proposed multimodal, pre-emptive analgesia protocol for paediatric post-tonsillectomy pain results in less post-operative pain, both in hospital or at home.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 32 publications
0
14
0
2
Order By: Relevance
“…Basic level • Intravenous fentanyl in divided doses • Rectal NSAID or if not available rectal paracetamol after induction of anesthesia or oral paracetamol or NSAID as a part of premedication (preemptive analgesia). 164 • Local wound infiltration by the surgeon of a long-acting local anesthetic. 60,139,[165][166][167][168][169] • Intravenous fentanyl or morphine or other suitable agent (if available) to treat breakthrough pain in the PACU 51,[170][171][172] • Oral NSAIDs and/or paracetamol in adequate dosage during the entire postoperative period from the moment when the oral intake will be possible.…”
Section: Intraoperative Postoperativementioning
confidence: 99%
“…Basic level • Intravenous fentanyl in divided doses • Rectal NSAID or if not available rectal paracetamol after induction of anesthesia or oral paracetamol or NSAID as a part of premedication (preemptive analgesia). 164 • Local wound infiltration by the surgeon of a long-acting local anesthetic. 60,139,[165][166][167][168][169] • Intravenous fentanyl or morphine or other suitable agent (if available) to treat breakthrough pain in the PACU 51,[170][171][172] • Oral NSAIDs and/or paracetamol in adequate dosage during the entire postoperative period from the moment when the oral intake will be possible.…”
Section: Intraoperative Postoperativementioning
confidence: 99%
“…El-fattah et al also demonstrated in post-tonsillectomy paediatric patient that postoperative pain measure scores of control group children were significantly higher within the first 3 post-operative days (p = 0.000), with a greater percentage of children experiencing significant pain and requiring more analgesia then study group who received pre-emptive analgesia. [30] Acute pain results in sympathetic over activity which is manifested by increase in heart rate, blood pressure, peripheral resistance and cardiac output. [31] In this present study, heart rate and blood pressure remained stable throughout the study period in Gr.…”
Section: Discussionmentioning
confidence: 99%
“…Die Autoren errechneten eine gute Korrelation zwischen den Messinstrumenten und beurteilten sie als gleichwertige Skalen [45]. El-Fattah et al verwendeten den PPPM, um ein präemptives Tripel-Analgesie-Protokoll bei Kindern zwischen 5 und 12 Jahren nach TE zu untersuchen [46]. Wir verwendeten in dieser Studie erstmals die deutsche Version dieser Beobachtungs-Skala zur Einschätzung von Schmerzen nach Tonsillektomien.…”
Section: Diskussionunclassified